Intraoperative MRI-guided neurosurgery - Hall, Walter A., 1957-; Nimsky, Christopher; Truwit, Charles L. (Thieme, 2011)
"Intraoperative MR-Guided Neurosurgery contains detailed coverage of this state-of-the-art technology from the pioneers who developed it. World-renowned neurosurgeons and neuroradiologists combine their collective wisdom and experience to demonstrate how MR-guided neuronavigation can be used to view real-time images of a patient's brain during surgery to help remove tumors with greater precision. The authors provide step-by-step descriptions of how to perform procedures, including advice based on their clinical results. Readers will learn about the advantages and drawbacks of the various MR imaging systems, clinical indications for MR-guidance, anesthesia considerations, safety concerns related to working in a magnetic environment, and much more"--Provided by publisher